CHEMICAL AND ORGANOLEPTIC QUALITY OF BALI BEEF INJECTED GROWTH PROMOTER - Rukmini, Ni Wayan Ayu; Swacita, Ida Bagus Ngurah; Suwiti, Ni Ketut; Besung, I Nengah Kerta (Buletin Veteriner Udayana, 2022)
Research on the effect of growth promoter on the chemical and organoleptic quality of Bali beef has been carried out. This experimental study used a completely randomized design with two treatments, namely cows that were given a growth promoter and control cows (without being given a growth promoter) and two types of meat, namely sirloin and shank. The research was repeated six times. A total of 24 samples from 12 male Bali cows aged 18 months were given a growth promoter and no growth promoter. Tests were carried out on chemical quality (protein, fat, water content) and organoleptic quality (color, aroma, texture and consistency). The results showed that injection growth promoter can increase levels of fat and crude protein and reduce water content of sirloin and shank. Growth promoter injection gave better color and texture, but had no effect on the consistency and aroma of Bali beef.